2018
DOI: 10.1002/bdm.2108
|View full text |Cite
|
Sign up to set email alerts
|

Do process simulations during episodic future thinking enhance the reduction of delay discounting for middle income participants and those living in poverty?

Abstract: Two studies examined whether episodic future thinking (EFT; pre‐experiencing future events) reduces discounting of future rewards (DD). No studies have investigated whether process simulations (i.e., simulating the process of executing a future event) amplify EFT's reduction of DD. Study 1 examined the effect of incorporating process simulations into EFT (N = 42, Mage = 43.27; 91% female, family income = $75,976) using a 2 × 2 factorial design with type of episodic thinking (process, nonprocess/general) and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Goal-directed process EFT and general EFT helped mothers purchase fewer calories in an online grocery store, with no differences in calories purchased between the EFT GDP and the EFT GEN group (η p 2 = .166 vs. η p 2 = .133, p = 0.69). Therefore, EFT GDP does not improve calorie outcomes beyond EFT GEN. Our findings were contrary to our expected hypothesis, but consistent with research showing similar changes in delay discounting for EFT process and EFT general cues for adults (O'Donnell et. al, 2018).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Goal-directed process EFT and general EFT helped mothers purchase fewer calories in an online grocery store, with no differences in calories purchased between the EFT GDP and the EFT GEN group (η p 2 = .166 vs. η p 2 = .133, p = 0.69). Therefore, EFT GDP does not improve calorie outcomes beyond EFT GEN. Our findings were contrary to our expected hypothesis, but consistent with research showing similar changes in delay discounting for EFT process and EFT general cues for adults (O'Donnell et. al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…Participants generated three cues with the content of the cue varying dependent on their group assignment. The intervention group in Study 1 was the EFT group with goal-directed process-oriented cues, which is a combination of two kinds of future-oriented cues that have been studied by our laboratory -goal-directed cues (O'Donnell, Daniel, & Epstein, 2017) and process-oriented cues (O'Donnell et. al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…over the next 24 hours) [20], no control cues [2125], cues generated based off of standardized reading material [14, 26] or cues about what money could buy [27]. There were also cues about meals eaten in the recent past [15] and recent/past events that ranged in time from 60 hours [28] to 12 days ago [29] and different time periods in-between [13, 3033]. Effect sizes varied from Hedge’s g = 0.26 [26] to 1.40 [14] (Table 1 provides more details) .…”
Section: Introductionmentioning
confidence: 99%
“…As a personality characteristic, for example, concern for future consequences of actions has been linked to better financial management (Joireman et al, 2005) and more frequent pro-environmental behaviors (Joireman et al, 2001(Joireman et al, , 2004. Strikingly, interventions that increase future-oriented thinking can reduce higher delay discounting rates (Daniel et al, 2013a(Daniel et al, , 2013bO'Donnell et al, 2019;Peters & Büchel, 2010) which we have shown are associated with poorer outcomes in the single-player game used here (Rauwolf & Rogers, under review). In a resource-management context, knowledge of the prospective resource availability might be increasing awareness of the need to work over a highlighted future, fostering better learning of resource dynamics and, in turn, better outcomes.…”
Section: Discussionmentioning
confidence: 78%